Pengaruh Konsentrasi dan Interval Waktu Pemberian BRE-4 terhadap Pertumbuhan dan Produksi Tanaman Pakcoy (Brassica rapa L.) serta Pemanfaatannya sebagai Leaflet - Umi Azizah Zein (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to determine the effect f concentration and application interval of BRE-4 on the groth and production of pak choy (Brassica rapa L.), as well as to develop the research finding into an informative printed printed medium in the form of a leaflet. Pak Choy is a horticultural commodity currently facing productivity declines due to deteriorating soil quality and pest exposure. BRE-4 is a modern fertilizer containing rhizobacteria and endophytic bacteria, serving as an alternative to pesticides for controlling pests and nematodes. The research was conducted at the Agrotechnopark Greenhouse, University of Jember, from June 2025 to August 2025, using a Factorial Completely Randomized Design (CRD). The treatment involved four concentration levels of BRE- K0 (0 ml/L), K1 (5 ml/L), K2 (10 ml/L), dan K3 (15 ml/L), and three time intervals I1 (every 2 time), I2 (every 4 time), dan I3 (every 6 time) with three replications. Observation parameters included growth, production, and abiotic factors, with data analyzed through ANOVA and DMRT tests at a 5% significance level. Leaflet validation was performed by material experts, media experts, and users. The results indicated that the combination of 10 ml/L concentration and a 4-day interval (K2I2) improved growth parameters, including a plant height of 31.42 cm, 13.97 leaves, a leaf area of 99 (𝑐𝑚2), a fresh weight of 100.42 grams, and a dry weight of 7.80 grams. Furthermore, production parameters reached a consumption weight of 96.62 grams and a harvest index of 96.20%. Furthermore, the developed leaflet was declared highly feasible by validators with a feasibility score of 84%, indicating it is an effective and practical informative medium. This research contributes to the use of BRE-4 fertilizer as a safe and enviromentally friendly as a subtitute fo hazardous chemical fertilizer.
FINALISASI oleh Arif 2026 Mei 26
Keywords: BRE-4; Concentration; Application Interval; Pok choy